Complements Are Not Always a Good Thing: Novel Therapies for Angioedema. (April 2016) - Bailey, Abby Mynatt; Reed, Brittany S.; Weant, Kyle A.; Justice, Stephanie Baker
Abstract : Hereditary angioedema attacks are rare, but emergency care providers must be aware of the clinical presentation and treatment of these patients because the emergency department remains the most common setting where these patients seek treatment. If providers are not aware of the past medical history of these patients, they are likely to receive standard therapies for respiratory distress and anaphylaxis including antihistamines, corticosteroids, and epinephrine. However, these medications may not work in these patients, given the pathophysiology of their underlying disease. Since 2009, several new therapies have been approved for the treatment of acute hereditary angioedema attacks. This article discusses pathophysiology, clinical presentation, and use of novel therapies for the management of angioedema.